Generalized Kudryashov method for nonlinear fractional double sinh-Poisson equation - Demiray, Seyma Tuluce; Bulut, Hasan (Int Scientific Research Publications, 2016)
Using the generalized Kudryashov method (GKM), we derive exact solutions of the nonlinear fractional double sinh-Poisson equation. We obtain novel dark soliton solutions. Some numerical simulations were done to see the behavior of these solutions. (C) 2016 All rights reserved.
Keywords: Nonlinear fractional double sinh-Poisson equation; generalized Kudryashov method; travelling wave transformation; dark soliton solution